Notes on the care, restoration and repair of microsurgical instruments - Robert, D Acland (Indian Journal of Plastic Surgery, 2006)
The high cost of microsurgical instruments is multiplied by failure to care for them appropriately. This paper describes effective practical measures for the care of microsurgical instruments; and shows detailed procedures for restoring and repairing the instruments most often damaged: jewelers′ forceps and scissors.
Keywords: Micro instruments; restoration; repair